1995
DOI: 10.1098/rspb.1995.0020
|View full text |Cite
|
Sign up to set email alerts
|

Low reproductive output of isolated, self-fertilizing snails: inbreeding depression or absence of social facilitation?

Abstract: Inbreeding depression has been studied extensively in m any anim als, but the potential of 'social facilitation' (a response to the presence of conspecifics in the environm ent) to influence reproduction has received little attention. Studies of reproductive o u tp u t in freshw ater herm aphrodite snails have im plicated inbreeding depression, but never social facilitation, in the reduced reproductive o utput of isolated com pared with p aired /g ro u p ed snails. In this experim ent, isolated, self-fertilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…She found that individuals of Biomphalaria glabrata prevented from outcrossing, but in the presence of a conspecific, had higher fecundity and hatching rates than isolated, selfing snails. While previous studies have indeed confounded effects of the mating system (selfing or outcrossing) and experimental condition (isolation or pairing), Vernon's (1995) study seems far from definitive because of low sample size, unusually low hatching success, and the use of strains that had been maintained in the laboratory for numerous generations. Thus, the generality of her results is difficult to evaluate without additional studies using appropriate designs.…”
Section: The Experimental Approach In Freshwater Pulmonatesmentioning
confidence: 93%
See 1 more Smart Citation
“…She found that individuals of Biomphalaria glabrata prevented from outcrossing, but in the presence of a conspecific, had higher fecundity and hatching rates than isolated, selfing snails. While previous studies have indeed confounded effects of the mating system (selfing or outcrossing) and experimental condition (isolation or pairing), Vernon's (1995) study seems far from definitive because of low sample size, unusually low hatching success, and the use of strains that had been maintained in the laboratory for numerous generations. Thus, the generality of her results is difficult to evaluate without additional studies using appropriate designs.…”
Section: The Experimental Approach In Freshwater Pulmonatesmentioning
confidence: 93%
“…Moreover, Vernon (1995) recently claimed that an absence of "social facilitation", rather than inbreeding depression, might be responsible for the low fecundity and poor hatching success in isolated individuals of primarily outcrossing freshwater pulmonates. She found that individuals of Biomphalaria glabrata prevented from outcrossing, but in the presence of a conspecific, had higher fecundity and hatching rates than isolated, selfing snails.…”
Section: The Experimental Approach In Freshwater Pulmonatesmentioning
confidence: 99%
“…Animals which can reproduce asexually may nevertheless have higher reproductive output in the presence of other individuals (Thomas and Benjamin 1973). In selffertile snails, Biomphalaria glabrata, and parthenogenetic female lizards, Cnemidophorus uniparens, individuals housed in isolation produce fewer offspring than individuals housed in groups, apparently because of exposure to courtship behaviour, although they do not actually mate (Crews et al 1986;Vernon 1995). It is not clear what effect this might have in nature (if any), but it is interesting and counter-intuitive that even species which are self-fertile have the potential to suffer from reproductive Allee effects, particularly since self-fertilisation itself may be an evolutionary adaptation to avoid Allee effects-this is discussed further below.…”
Section: Physiological Stimulationmentioning
confidence: 99%
“…We noted social facilitation of noncolonial snail behavioral responses to predator þ alarm cues, as snails responded more strongly to the cue when conspecifics were present. In a broad sense, snails are capable of learning and memory formation [35] and also display social effects on reproduction [10], feeding [36], and direction of movement [37]. It is possible, then, that the response of a snail to predators may initiate or increase the predator response of other nearby snails.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, gastropods are very responsive to biological cues from predators [8,9], and evidence suggests that they respond to conspecific cues as well, because self-fertilizing snails become reproductive sooner when reared with conspecifics but separated by a water-permeable barrier [10]. Because freshwater gastropods are seeing more widespread use in ecotoxicology studies [11][12][13] and also are being developed as potential test organisms for endocrine-disrupting chemicals [14,15], understanding how the presence of conspecifics impacts response to stressors in gastropods is important for optimizing experimental designs and in understanding the implications of certain study design characteristics.…”
Section: Introductionmentioning
confidence: 99%